Microbial contamination and purification of bivalve shellfish: crucial aspects in monitoring and future perspectives - a mini-review - Oliveira, J. (2019)
Shellfish are a nutritious food source whose consumption and commercial value has risen dramatically worldwide. Although bivalve’s consumption can contribute to a healthy diet, some can cause foodborne illnesses. Microbial contamination is chronic and pervasive in harvesting areas and may be passed on to the consumers. Current food safety programs intend to protect consumers. Nevertheless, bivalve’s microbial contamination is underestimated and undermanaged, which can pose a potential public health risk. We intend to provide an updated overview of the microbial assessment of bivalves and emerging alternatives or complementary perspectives for the elimination of microbial contamination. Further research is needed for the improvement of public health control and the enhancement of shellfish safety.